Analisis Dakwah Digital Felix Siauw Sebagai Pendakwah dan Influencer - Dzaki Anshari, Muhammad; Nirwan Syafrin; Rosmawati (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
Da’wah as a public speaking activity always requires digitalization. Today’s developments which lead society to grow together with advances in technology and information require massive digitalization of information in an effort to convey messages well. Digitizing da’wah messages is one form of effort to maintain da’wah in people’s lives, especially in the digital era. Felix Siauw, as a well-known digital preacher with 5.3 million followers on his Instagram social media account, is able to influence society regarding the idea of "hijrah" or changing to a better Muslim personality. This research was carried out using a qualitative-descriptive methodby using a content analysis table for audio-visual preaching and library sources as a medium for describing research objects; Felix Siauw’s digital preaching. Digital literature sources were also used in an effort to find ideas, thoughts and opinions in this research. The results of this research show that there are 9 da’wah topics that Felix Siauw often uses in carrying out digital da’wah, namely; Thought, Islamic Morals, Worship, Hijrah, Islamic History, Politics, Marriage, Youth, Faith Motivation. The da’wah topics raised by Felix Siauw are presented in 4 various forms of digital media output, namely; images with captions, animated videos and audio, illustrated videos and audio, and video recordings of preaching messages. In all forms of digital da’wah that have been produced on Instagram, Felix Siauw uses 4 types of approaches; delivery of advice and stories of experiences, only delivery of advice, delivery of advice and discussion, and only discussion.